Quasi-periodic photonic crystal Fabry–Perot optical filter based on Si/SiO2 for visible-laser spectral selectivity. (8th May 2018) - Qi, Dong; Wang, Xian; Cheng, Yongzhi; Chen, Fu; Liu, Lei; Gong, Rongzhou
Abstract: We report on a 1D quasi-periodic photonic crystal Fabry–Perot optical filter Cs (Si/SiO2 ) 3 (SiO2 /Si) 3 for spectral selectivity of visible light and 1.55 µ m laser. A material transparency interval of 1.03–2.06 µ m makes Si a unique choice of high refractive index material. Owing to the CIE 1931 standard and equal inclination interference, the designed structure can be successfully fabricated with a certain color (brown, khaki, or blue) corresponding to the different Cs physical thickness d and response R ( λ ). In addition, the peak transmittance T max of the proposed structure can reach as high as 92.56% (Cs = 20 nm), 90.83% (Cs = 40 nm), and 88.85% (Cs = 60 nm) with a relatively narrow full width at half maximum of 4.4, 4.6, and 4.8 nm at 1.55 µ m. The as-prepared structure indicates that it is feasible for a photonic crystal Fabry–Perot optical filter to achieve visible-laser (1.55 µ m) spectral selectivity.